2001
DOI: 10.1001/jama.285.6.748
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Oseltamivir in Preventing Influenza in Household Contacts<SUBTITLE>A Randomized Controlled Trial</SUBTITLE>

Abstract: In our sample, postexposure prophylaxis with oseltamivir, 75 mg once daily for 7 days, protected close contacts of influenza-infected persons against influenza illness, prevented outbreaks within households, and was well tolerated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
244
0
21

Year Published

2002
2002
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 431 publications
(273 citation statements)
references
References 25 publications
8
244
0
21
Order By: Relevance
“…It has been reported that 75-80% of household transmissions occur directly from the influenza-positive index patient or from the same source of infection as the index patient. 7,8 In this group, all of the clinical secondary cases have an influenza aetiology. The remaining 20-25% are due to transmission from the community at large.…”
Section: Strengths and Limitationsmentioning
confidence: 93%
See 3 more Smart Citations
“…It has been reported that 75-80% of household transmissions occur directly from the influenza-positive index patient or from the same source of infection as the index patient. 7,8 In this group, all of the clinical secondary cases have an influenza aetiology. The remaining 20-25% are due to transmission from the community at large.…”
Section: Strengths and Limitationsmentioning
confidence: 93%
“…This definition is based on the criteria that define influenza-like illness in clinical trials of neuraminidase inhibitors. 7,8,13 Household contacts who developed clinical influenza within 5 days of the initial visit of the index patient were classified as secondary patients.…”
Section: What Does This Paper Add?mentioning
confidence: 99%
See 2 more Smart Citations
“…39 Also, post -exposure prophylaxis with oseltamivir, 75 mg once daily for 7 days, was found to protect close contacts of infl uenza -infected persons against infl uenza illness and prevented spread within households. 40 Post -exposure prophylaxis with oseltamivir can be considered an effective option for preventing the transmission of infl uenza within households. 41 It should be recognized, however, that oseltamivir is less effective against infl uenza B than against infl uenza A -that is, with regard to duration of fever and virus persistence.…”
Section: Neuraminidase Inhibitors: Zanamivir and Oseltamivirmentioning
confidence: 99%